Changes in Tobacco Use During the 2020 COVID-19 Lockdown in New Zealand - Gendall, Philip (Nicotine Tob Res, 2021)
INTRODUCTION: New Zealand’s response to the COVID-19 pandemic was one of the most restrictive lockdowns of any country, inevitably causing stress for many people. Because situations that increase stress and anxiety are associated with higher smoking prevalence, we examined self-reported smoking before and during the lockdown, and analyzed factors associated with reported changes in cigarette consumption. AIMS AND METHODS: We conducted an online panel survey of a demographically representative sample of 2010 adult New Zealanders during the COVID-19 lockdown; the final, weighted sample included 261 daily smokers and 71 weekly smokers. We measured psychological distress and anxiety, as well as situational factors, tobacco consumption, and demographic attributes. RESULTS: Nearly half of daily smokers reported smoking more during than before the lockdown, on average, an increase of six cigarettes a day; increased daily cigarette consumption was associated with loneliness and isolation. Most weekly smokers reported either that their smoking during the lockdown had not changed or had slightly reduced. CONCLUSIONS: Smoking cessation services need to anticipate that unexpected disruptions, such as pandemic lockdowns, may be associated with increased daily tobacco consumption, and that this increase may be sustained after lockdown. While public health responses to pandemics predictably focus on immediate and obvious consequences, interventions to support recent quitters and those making quit attempts should also form a key component of pandemic planning. IMPLICATIONS: As governments introduce unprecedented measures to manage COVID-19, they need also to consider other public health risks, such as increased smoking among current smokers or relapse among recent quitters. Evidence that loneliness was associated with increased smoking during a lockdown suggests a need for cessation out-reach strategies that promote and support smoke-free practices.